2018
DOI: 10.3390/v10080415
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition but Not Curvature Is the Determinant Factor for the Low Molecular Mobility Observed on the Membrane of Virus-Like Vesicles

Abstract: Human Immunodeficiency Virus type-1 (HIV-1) acquires its lipid membrane from the plasma membrane of the infected cell from which it buds out. Previous studies have shown that the HIV-1 envelope is an environment of very low mobility, with the diffusion of incorporated proteins two orders of magnitude slower than in the plasma membrane. One of the reasons for this difference is thought to be the HIV-1 membrane composition that is characterised by a high degree of rigidity and lipid packing, which has, until now… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…Twochannel FCS acquisitions permit the simultaneous calculation of diffusion coefficients and lipid packing by means of the GP function. By employing this approach, we found that the lipid packing and bilayer dynamics anticorrelate in model and live-cell membranes, suggesting that the slow diffusion coefficients commonly measured in plasma membranes can be ascribed to the high degree of lipid packing of this structure, which arises from its distinct lipid composition 50 , as previously suggested for highly packed viral membranes 52 .…”
Section: Sted-fcs Measurements Show Superior Resolution Of Nr4a and Nr12a Compared Tosupporting
confidence: 62%
“…Twochannel FCS acquisitions permit the simultaneous calculation of diffusion coefficients and lipid packing by means of the GP function. By employing this approach, we found that the lipid packing and bilayer dynamics anticorrelate in model and live-cell membranes, suggesting that the slow diffusion coefficients commonly measured in plasma membranes can be ascribed to the high degree of lipid packing of this structure, which arises from its distinct lipid composition 50 , as previously suggested for highly packed viral membranes 52 .…”
Section: Sted-fcs Measurements Show Superior Resolution Of Nr4a and Nr12a Compared Tosupporting
confidence: 62%
“…How enveloped viruses acquire their lipid membrane shell is of great importance for their biogenesis and their capacity to infect cells. In the case of HIV-1, recently, it has been shown that the envelope lipid composition was a determinant of low molecular mobility of the Env protein ( 3 , 16 ). Several works have been conducted to reveal different envelope viruses having their own unique lipid composition ( 2 , 7 , 9 , 42 ), implying their distinct biological requirements during infection, and suggesting their capacity in sorting specific host lipids into their virus membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, recent advances in super-resolution microscopy techniques have enabled for the characterization of molecular mobility at the nanoscale, i.e., on the scale of individual (<140 nm) HIV-1 particles. For example, experiments using a combination of super-resolution [stimulated emission depletion (STED) microscopy and fluorescence correlation spectroscopy (STED-FCS) ( 13 ) or scanning STED-FCS (sSTED-FCS) ( 14 , 15 )] revealed a low mobility of molecules on the HIV-1 surface ( 3 ) due to the high degree of lipid packing in the virus membrane ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative system to lipid extraction is the use of artificial model membranes, i.e., membranes made of simple lipid mixtures that resemble the chemical and biophysical properties of the HIV lipid envelope. Imaging of artificial model systems has been employed to determine lipid dynamics and molecular order of virus-like membranes [14,55,56].…”
Section: Virus and Model Membranesmentioning
confidence: 99%